Self-archiving publications - Pinfield, Stephen (Facet Publishing, 2004)
This chapter discusses the historical development, current practice and future prospects of the self-archiving of research papers in open-access repositories (so-called 'e-print archives'). It describes how the development of interoperable e-print repositories in a number of subject communities has shown that self-archiving can benefit academic researchers (and potentially others) by enabling quick and easy access to the research literature and therefore maximising the impact potential of papers. Realising that the possible benefits are high and the technical entry barriers low, many organisations such as universities have recently tried to encourage widespread self-archiving by setting up institutional repositories. However, major barriers to self-archiving remain - most of them cultural and managerial. There are concerns about quality control, intellectual property rights, disturbing the publishing status quo, and workload. Ways in which these issues are currently being addressed are discussed in this chapter. A number of self-archiving initiatives in different countries have been set up to address the concerns and to kick-start e-print repository use. However, issues remain which require further investigation; those discussed in this chapter include discipline differences, definitions of 'publication', versioning problems, digital preservation, costing and funding models, and metadata standards. The ways in which these issues are resolved will be important in determining the future of self-archiving. Possible futures are discussed with particular reference to journal publishing and quality control. If widely adopted, self-archiving might come to assume a central place in the scholarly communication process, but a great deal of restructuring of the process needs to take place before this potential can be realised.